Can We Find the Washback Effects of International English Language Testing System on IELTS Learners? - Diki Riswandi; Didik Tri Wahyudi (University of Muhammadiyah Purwokerto, 2018)
IELTS test nowadays becomes one of the most important thing to get for those especially who want to continue their study in English speaking country especially UK or Australia. Because of the important roles of this standardized tests, it effects on students’ lives around the world. This study is conducted to find out the IELTS test influence on learners preparing for a test on learning and teaching outcomes and an obvious path for IELTS teachers in order to modify their methods and strategy of teaching. Therefore, the present study has tried to investigate whether IELTS preparation classes have any influence on the learning processes and the achievement of students in such an examination. To obtain the data, the writers used library research. A qualitative analysis was employed by identifying and classifying the finding of previous research of washback effects of the IELTS test toward the learners. It was found that there are positive and negative washback effects of IELTS test toward the learners.